Lean practices in machinery manufacturing industries – a case study. Issue 4 (1st January 2015) - Saleeshya, P.G.; Sneha, A.; Karthikeyan, C.; Sreenu, C.; Rohith, A.K.
Lean manufacturing is an emerging concept in the Indian manufacturing scenario. Many small and medium scale enterprises in the country are aiming at becoming lean and thereby improving their productivity. This paper is an outcome of a case study in one such enterprise that deals with the manufacturing and assembly of offset printing machinery in India. Being a vendor-based organisation, part shortage due to delays in the process was a major problem faced. A thorough analysis of the various vendors and processes that the product goes through was done and the process flow was mapped to obtain a clear picture of the entire system, and software modelling helped arrive at quantitative results. Lean tools like Pareto analysis, five-why analysis, source inspection, etc., were used to identify and eliminate the various factors that led to delay. Proper scheduling of jobs is also essential to reduce waiting time, and therefore an algorithm has been developed to help arrive at an optimum scheduling sequence. The results from this case study have proved successful in reducing the lead time of the component under study.